2021
DOI: 10.1108/md-12-2020-1592
|View full text |Cite
|
Sign up to set email alerts
|

A social cognition perspective on entrepreneurial personality traits and intentions to start a business: Does creativity matter?

Abstract: PurposeThis paper proposes and empirically assesses a social cognition conceptual model linking creativity (both artistic and scholarly), entrepreneurial personality traits, and entrepreneurial intention. Specifically, the study draws on social cognition perspectives to investigate the potential role of creativity as a mechanism underlying the relationship between entrepreneurial personality traits and entrepreneurial intention.Design/methodology/approachUsing a sample of 194 creative nascent entrepreneurs, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 91 publications
0
9
0
Order By: Relevance
“…Earlier studies on this sector and country have analyzed the psychological, emotional (Altinay et al. , 2021) and social cognitive (Altinay et al. , 2022) aspects of creative entrepreneurs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier studies on this sector and country have analyzed the psychological, emotional (Altinay et al. , 2021) and social cognitive (Altinay et al. , 2022) aspects of creative entrepreneurs.…”
Section: Methodsmentioning
confidence: 99%
“…In Kazakhstan, creative entrepreneurship is seen as a promising alternative to oil, gas and public sector employment for young people. Earlier studies on this sector and country have analyzed the psychological, emotional (Altinay et al, 2021) and social cognitive (Altinay et al, 2022) aspects of creative entrepreneurs. What these and other studies on creative entrepreneurship (Werthes et al, 2017) have highlighted as being sector-specific is the need for support policies aimed at creating a favorable environment.…”
Section: Methodology 41 Research Contextmentioning
confidence: 99%
“…More specifically, previous literature have indicated that person inputs like sharing achievement (Wu et al, 2021), as well as ESE (Santos and Liguori, 2020), and environmental inputs such as learning experiences (Bloemen-Bekx et al, 2019) play important roles in entrepreneurial intentions building on SSCT. Although SCCT provides a fruitful theoretical framework to understand how entrepreneurial intentions develop (Altinay et al, 2022;Liguori et al, 2018Liguori et al, , 2019, empirical validation and systemic understanding of the framework is relatively scarce when compared to other classic intention-based models (Brown and Lent, 2019;Lent and Brown, 2019). This study fills in this gap by exploring internal mechanisms and boundary conditions that matter for the relationship between family-work enrichment and entrepreneurial intentions.…”
Section: Social Cognitive Career Theorymentioning
confidence: 99%
“…, 2019) play important roles in entrepreneurial intentions building on SSCT. Although SCCT provides a fruitful theoretical framework to understand how entrepreneurial intentions develop (Altinay et al. , 2022; Liguori et al ., 2018, 2019), empirical validation and systemic understanding of the framework is relatively scarce when compared to other classic intention-based models (Brown and Lent, 2019; Lent and Brown, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Curiously, academic creativity is reported to encourage a more conservative approach to risk-taking. However, artistic creativity tends to improve EI (Altinay et al. , 2022).…”
Section: Literature Review and The Formulation Of This Study’s Hypoth...mentioning
confidence: 99%